Desenvolvimento de um ambiente de realidade virtual para estudo da perícia forense - Cover, Ari (2017)
This paper aims to present an immersive Virtual Reality environment for forensic study, which uses a methodology for communication between a real forensic database and this virtualenvironment. The aim was to create a tool that facilitates the forensic expert to study a simulated crime scene, based on a criminal investigation dataset. For the pilot study, we previously selected a crime scene from forensic literature and recreated it in a virtual environment, allowing navigation, selection and manipulation of 3D objects and information contained in the expert report. The association between the objects of interest and the collected evidence followed a predefined configuration and it stored in simple report records in CSV files. This configuration tends to be incorporated into a criminal expertise system under developing, whichmain business rule is to generate expert reports in digital format. The results obtained in preliminary evaluation of the virtual environment and data representation were positive, with contributions from a group composed of two medical experts, two criminal lawyers and two common users